2022
DOI: 10.3390/ma15103425
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Alumina-Spinel Refractory by Secondary Metallurgical Slag Using Coating Corrosion Test

Abstract: In this paper, the corrosion mechanism of commercial alumina-spinel refractory was investigated at 1350 and 1450 °C. Disc samples were coated with shells of two different slags containing 4 and 10 wt.% SiO2. The after-corrosion refractory was investigated in view of changes in its microstructure and phase composition by SEM/EDS and XRD techniques, respectively. At 1350 °C slags slightly infiltrated the microstructure, whereas at 1450 °C slags infiltrated the alumina-spinel refractory causing its significant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…From the analysis of thermodynamic simulation, it can be found that the high melting point phase CaAl 4 O 7 is the critical point in enhancing the slag resistance of the crucible [ 37 , 38 , 39 , 40 ]. The maximum content of the CaAl 4 O 7 of the CA 6 , Al 2 O 3 , and CA 6 -Al 2 O 3 crucible is 49.04%, 34.18%, and 40.11%, respectively, through the thermodynamic simulation results, which the trend is consistent with the EDS results.…”
Section: Resultsmentioning
confidence: 99%
“…From the analysis of thermodynamic simulation, it can be found that the high melting point phase CaAl 4 O 7 is the critical point in enhancing the slag resistance of the crucible [ 37 , 38 , 39 , 40 ]. The maximum content of the CaAl 4 O 7 of the CA 6 , Al 2 O 3 , and CA 6 -Al 2 O 3 crucible is 49.04%, 34.18%, and 40.11%, respectively, through the thermodynamic simulation results, which the trend is consistent with the EDS results.…”
Section: Resultsmentioning
confidence: 99%
“…Darban et al [15] revealed the corrosion of an alumina-spinel refractory against secondary steel slag via a coating corrosion test at 1350 • C and 1450 • C. They summarized the study by showing the passive corrosion mechanism of the refractory, with the formation of CA, CA 2 and CA 6 layers around the Al 2 O 3 core and C 2 AS in the matrix.…”
Section: Corrosionmentioning
confidence: 99%
“…Various types of calcium aluminate phases exist, such as C 3 A, C 12 A 7 , calcium monoaluminate (CA), calcium dealuminate (CA 2 ), and calcium hexaluminate (CA 6 ) [29,30], some of which can absorb sulfur. According to S. Kim et al [31], different calcium aluminate phases exhibit different sulfur capacities, with C 12 A 7 and C 3 A demonstrating superior performance.…”
Section: Introductionmentioning
confidence: 99%